HUBUNGAN KUALIFIKASI PENYULUH DENGAN KAPASITAS PENYULUH PERTANIAN DI KOTA KENDARI - Alhadi, Sahrul; Abdullah, Sukmawati; Salahuddin, Salahuddin (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2023)
The implementation of agricultural extension in the success of agricultural development in Indonesia needs to be supported by the ability of individual extension workers themselves in carrying out their duties as agricultural extension workers. So that the position of agricultural extension workers is an important position in the process of delivering and implementing agricultural extension programs in agricultural development. Therefore, extension workers are required to have the ability or capacity to carry out extension activities to the farming community. This study aims to determine: 1). the qualifications of extension workers with the capacity of agricultural extension workers 2). The relationship between the qualifications of extension workers and the capacity of agricultural extension workers in conducting extension activities in Kendari City. The basic research method used is quantitative with survey techniques. The location selection was done purposively in Kendari City. Sampling using census / saturated sampling technique and respondents taken as many as 63 agricultural extension workers. Data analysis using the spearman rank test. The results showed that: 1) the level of qualifications possessed by agricultural extension workers in Kendari City has fulfilled the capacity as an agricultural extension worker and 2) there is a significant relationship between the qualifications of agricultural extension workers and the capacity of agricultural extension workers in Kendari City.